T de Ayre modificada. Un aporte. - Rivas Sierra, José Alfredo; Sierra, Rivas; Alonso Moreno, Yolanda; Pérez, Lázara; Hernández, Clara; Cantero, Oria; Acosta, Cayetano; Jiménez, Luis (Revista Cubana de Pediatría, 2023)
Se realiza un estudio gasométrico con el propósito de respaldar esta sugerencia.